Biomechanical effects of endplate sagittal coverage change on cervical disc replacement: a finite element analysis - Chen, Lihua; Wang, Haiyan; Xu, Guangming; Liu, Hao (Frontiers in Bioengineering and Biotechnology, 2024)
Methods: A C2-C7 nonlinear finite element model of the cervical spine was established and validated. Based on the cervical spine model, cervical disc replacement surgery models were constructed with different distances of sagittal distance at the posterior edge of the upper prosthetic endplate (0, 1, 2, 3 mm, respectively) and sagittal distance at the posterior edge of the lower prosthetic endplate (1, 2, 3 mm, respectively). Each model was subjected to the same 1Nm torque and 73.6N driven compressive load. Range of motion (ROM), intervertebral disc pressure (IDP), facet joint force (FJF), and endplate stress were measured at the cervical surgical and other segments. Results: Compared to the intact cervical spine model, the sagittal distance of the posterior edge of the prosthesis endplate at different distances increased the stress on the intervertebral disc and the capsular joint in the adjacent vertebral body segments to different degrees, especially in extension. In different directions of motion, the posterior margin sagittal distance of the posterior edge of the endplate of the lower prosthesis has a greater mechanical influence on the cervical spine compared to the posterior margin sagittal distance of the posterior edge of the endplate of the upper prosthesis. Compared with the intact model, the biomechanical parameters (ROM, FJF, endplate stress) of the C5-C6 segment increased the most when the sagittal distance of the posterior edge of the endplate of the upper prosthesis was 3 mm, which were 64%, 56%, and 475%, respectively. Compared with the intact model, the maximum intervertebral disc stress of C4-C5 and C6-C7 was 0.57 MPa and 0.53 MPa, respectively, when the sagittal distance of the posterior edge of the upper prosthetic endplate was 3mm.After the sagittal distance of the posterior edge of the prosthetic endplate was completely covered, the mechanical influence of the entire cervical spine was low. The sagittal distance at the posterior edge of the endplate of different sizes changed the motion pattern and load distribution of the implanted segment to some extent.